Pb - Zn - Cu mineralization in the historical Broumov - Tri Sekery mining district (Western Bohemia) - Maly,K.D.; Zacharias,J.; Pertold,Z. (Journal of the Czech Geological Society, 2005)
A mineralogical and geochemical study has been carried out of the historical Pb-Zn-Cu Broumov - Tri Sekery mining district in the northern part of the Cesky les valley, in the vicinity of the boundary between the Moldanubian and Saxothuringian units. Sulphide mineralization of NW-SE and NE-SW trending quartz veins was formed in three stages: 1) early alteration related stage: chlorite, tourmaline and quartz; 2) main stage: quartz, galena, sphalerite, chalcopyrite and pyrite; and 3) late fracture related stage: quartz, chalcopyrite and minor galena, sphalerite, pyrite, gersdorffite and unidentified Bi-Co-Ni-As minerals. Formation temperatures of approx. 270-280 (±25) °C and 230-115 °C are suggested for the early and main stages, respectively. Fluid salinities vary from 10.8 to 16.9 and from 21.2 to 23.7 wt. % eq. NaCl for quartz and sphalerite of the main stage, respectively. The sulfur isotope composition of the main stage sulphides varies from -5.0 to +5.8 (‰ vs. CDT). Barren banded quartz veins (quartz and amethyst), related to NNW-SSE trending tectonic zones, contain only one-phase liquid fluid inclusions. Consequently, their formation temperatures are interpreted lower than 50-60 °C.
Keywords: Ore mineralization; base-metals; fluid inclusions; chlorite thermometry; sulphur isotopes